ANALISIS RAWAN KEKERINGAN DI DESA GIRICAHYO, KECAMATAN PURWOSARI, GUNUNG KIDUL - Hasmaulia, Qaanitah (Universitas Nusa Cendana, 2025)
This study analyzed drought vulnerability levels in Giricahyo Village, Gunungkidul Regency, Special Region of Yogyakarta, using a Geographic Information System (GIS) approach. The karst area, characterized by porous geological features, results in limited surface water availability, particularly during the dry season. The research method involved collecting spatial and non-spatial data, including rainfall, soil type, slope gradient, geology, and land use, which were processed using GIS-based overlay techniques. The results showed that Giricahyo Village is classified into five drought vulnerability levels, dominated by low (7.986 km²) and moderately low (4.897 km²) vulnerability, while high vulnerability (1.598 km²) was found in steep-sloped areas with porous Lithosol soil. The primary contributing factors were the combination of steep slopes, Lithosol soil, and suboptimal rainwater absorption due to karst geology. Field validation confirmed a 42.5% consistency between predictions and actual conditions, with discrepancies mainly in areas with piped water supply (PAM) infrastructure. Community adaptation through rainwater harvesting and clean water distribution proved effective in mitigating drought impacts. This study recommends drought mitigation-based spatial planning and sustainable water resource management for karst region.